Effect of eccentric load on retrofitted reinforced concrete columns confined with FRP - Pham, Thong; Lei, X.; Hadi, M. (2013)
Different behaviour of diverse sections of confined Reinforced Concrete (RC) columns under eccentric load is investigated in this study. Three types of sections are considered, which include square columns, square with rounded corners and modified circular columns. Twelve reinforced square concrete columns were made from normal strength concrete and subdivided into four groups. The first three columns were the Reference Group and had no modification.The next three columnswere modified with round corners and wrapped with three layers of Carbon Fibre Reinforced Polymer (CFRP), another three were bonded with four pieces of segmental circular concrete covers and wrapped with three layers of CFRP, and the last three were bonded with concrete covers and confined with steel straps. All columns were tested under concentric loading, 15mm and 25mm eccentric loading. Results from the study show that all confinement methods increase capacity and ductility of columns, in which segmental circular concrete covers considerably reduce the stress concentration on the corners and increase the efficiency of the confinement. Effect of eccentric load on the specimens wrapped with FRP is significantly higher than the Reference Group. © 2013 Taylor & Francis Group.